2018
DOI: 10.1007/s11356-018-2783-7
|View full text |Cite
|
Sign up to set email alerts
|

Hotspots and main drivers of fecal pollution in Neusiedler See, a large shallow lake in Central Europe

Abstract: To minimize the risk of negative consequences for public health from fecal pollution in lakes, the continuous surveillance of microbiological water quality parameters, alongside other environmental variables, is necessary at defined bathing sites. Such routine surveillance may prove insufficient to elucidate the main drivers of fecal pollution in a complex lake/watershed ecosystem, and it may be that more comprehensive monitoring activities are required. In this study, the aims were to identify the hotspots an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 44 publications
(63 reference statements)
0
10
0
3
Order By: Relevance
“…Otherwise, the southern wind disturbs the movement from the northern area to the southern area. The wind direction and speed have dramatically influenced water circulation and the spread of microbial contamination in various bodies of surface water [39][40][41]. Sokolova et al [42] concluded that the microbial contamination from different sources was transported faster or slower to the water intake, depending on the wind speed and direction.…”
Section: Discussionmentioning
confidence: 99%
“…Otherwise, the southern wind disturbs the movement from the northern area to the southern area. The wind direction and speed have dramatically influenced water circulation and the spread of microbial contamination in various bodies of surface water [39][40][41]. Sokolova et al [42] concluded that the microbial contamination from different sources was transported faster or slower to the water intake, depending on the wind speed and direction.…”
Section: Discussionmentioning
confidence: 99%
“…There is a strong economic interest in the lake and the surrounding national parks due to their recreational value 1,5 . Thus, the lake’s water quality, including potential pathogenic microbes, is monitored on a regular basis 69 . Nevertheless, the bacterial community composition of water and sediment remains largely unexplored, particularly in relation to the lakes’ hydrochemistry.…”
Section: Background and Summarymentioning
confidence: 99%
“…Schwarze Linien in den Boxen -Median; Ausreißer und Extremwerte sind mit kleinen Kreisen angezeigt. Modifiziert nach Hatvani et al (2018) Falle zur Einstufung "bedenklich" führte (Löffler und Kohl 1982).…”
Section: Neusiedler See -Anfänge Eines Monitoringsunclassified
“…Diese Werte wurden ausgewählt, da sie in der Österreichischen Badegewässerverordnung als Grenzwerte für kurzfristige Verschmutzungsereignisse festgelegt sind (Österreichische Badegewässerverord-nung 2009, idgF.). Als Wetterereignisse wurden jene Messdaten betrachtet, bei denen die täglichen Niederschlagsmengen oder maximalen Windgeschwindigkeiten in der statistischen Analyse als Ausreißer oder Extremwerte eingestuft wurden (Hatvani et al 2018;Kirschner et al 2018 Trotz der großen Bedeutung, die extreme Wetterereignisse und im Speziellen extreme Niederschlagsereignisse auf die mikrobiologisch-hygienische Wasserqualität des Neusiedler Sees haben, darf nicht übersehen werden, dass nur etwa 30-35 % aller an den Hotspots beobachteten Verschmutzungsereignisse auf extreme Niederschläge zurückzuführen waren, ein großer Anteil (etwa 40 %) nicht durch Niederschlags-bzw Wetterereignisse erklärt werden konn-te. Lokale Besonderheiten spielen bei jedem Hotspot eine Rolle, aber auch der an schönen Tagen große Besucherandrang (Badegäste, Surfer, Segler), der direkt (Ausscheidungen im See) oder indirekt (über erhöhte Abwassereinleitungen aus den Kläranlagen Podersdorf, Jois) zu einer erhöhten fäkalen Belastung im See führen kann.…”
Section: Neusiedler See -Anfänge Eines Monitoringsunclassified
See 1 more Smart Citation